Analisis Konsep Keadilan Restoratif (Restorative Justice) dalam Kasus Penggunaan Hukuman Disiplin (Corporal Punishment) pada Anak di Lingkungan Sekolah Ditinjau dalam Perspektif Perlindungan Guru - Raynel Matheus Kapioru; Jimmy Pello; Reny Rebeka Masu (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Discipline in education is necessary for students to understand moral and social boundaries. The practice of disciplining (corporal punishment) against students is still debatable. Some people consider it a form of violence against children that contradicts the principles of child protection in Law Number 35 of 2014 concerning Child Protection. A dilemma arises regarding the limits of the teacher's authority in disciplining students and whether these actions can be categorized as criminal acts or are still included in the realm of education. Article 14 of Law No. 14/2005 on Teachers and Lecturers states that teachers have the right to impose sanctions on students who violate norms, rules, and academic ethics. This research is normative research. The results of this research are: (1) The provision of corporal punishment by teachers against students who violate religious norms, norms of decency, norms of politeness, written and unwritten rules set by teachers in the learning process cannot be categorized as acts against criminal law if the corporal punishment carried out by the teacher does not exceed the limits of reasonableness or punishment that is educational in nature in accordance with the teacher's code of ethics. (2) The application of mediation as a form of protection for teachers regulated in Article 4 paragraph 2 of Permendikbud Number 10 of 2017, where mediation is a form of implementation of restorative justice values creating a space for peaceful problem solving that considers the interests of students, teachers and students. The application of mediation as a form of protection for teachers regulated in Article 4 paragraph 2 of Permendikbud Number 10 of 2017, where mediation is a form of implementation of restorative justice values creating a space for peaceful problem solving that considers the interests of students, teachers, and the school community.